Analisis Proses Penalaran Capaian Pembelajaran untuk Diturunkan menjadi Tujuan Pembelajaran di SDN Poris Plawad 5 Kota Tangerang - Magdalena, Ina; Sharmadi, Bella Shadila; Rosadah, Rosadah (YASIN, 2023)
In education, the following are the general components of the curriculum: objectives, material or content, process or delivery system, media, and evaluation. Islamic Religious Education and Character Education, Pancasila Education, Indonesian Language, Mathematics, and Natural and Social Sciences (IPAS) are the five primary school subject areas covered by the Merdeka Curriculum. Of course, there are four different curriculum components for each subject area. To achieve learning outcomes in each subject, everything becomes an inseparable unit. This is intended as reading material to understand each part of the subject, especially the contents of the five subject areas taught in elementary schools.